Sustainability Water Index (ISA) for Peruvian River Basins - Aguirre-Núñez, Mario (2025)
The article presents a methodological proposal for assessing water sustainability in river basins using the Water Sustainability Index (WSI) and its application in the river basins of Chili, Caplina, Chancay-Lambayeque, and Urubamba, as well as at the national level in Peru, for the period 2012-2021. The WSI consists of three sub-indices based on the components of sustainable development: economic (SiE), social (SiS), and environmental (SiA). The WSI rating scale ranges from 0 (lowest) to 100 (highest). Intrinsic and extrinsic indicators, both economic, social, and environmental, were selected. The results show that, both at the basin level and nationally, the social component performs best. However, significant challenges remain in the environmental component (Caplina and Chili river basins) and the economic component (Chancay-Lambayeque, Chili, Urubamba river basins, and national level). Additionally, the risk of water unsustainability is linked to both physical factors (water scarcity in the Caplina basin) and management issues (in the Chancay-Lambayeque basin).